Strategi Guru Pendidikan Agama Islam dalam Menanamkan Nilai-nilai Ibadah di Madrasah Ibtidaiyah Ma’arif Polorejo Babadan Ponorogo - Hepy Kusuma Astuti (IAIN Ponorogo, 2022)
The values of worship as a form of fostering Islamic religious education in Madrasahs are an effort to create quality human resources, so that they are able to compete in the era of globalization as is happening today while still upholding the teachings of Islam. For this reason, the teacher as the main actor in instilling religious and religious values to students requires certain strategies so that the values of worship can be absorbed and become part of the daily lives of students. Therefore, this study aims to determine the values of worship that are instilled in Madrasah Ibtidaiyah Ma'arif Polorejo, Babadan District, Ponorogo Regency and to find out the strategy of PAI teachers in instilling worship values. This study employed descriptive qualitative method, primary data was obtained through the method of observation, interviews, and documentation on the MI Ma'arif Polorejo teachers and related documents. The results of this study found that the values of worship instilled in MI Ma'arif Polorejo were, the value of piety, the value of discipline, the value of patience, and the value of honesty. Then, the strategy used by PAI teachers in instilling the value of worship at MI Ma'arif Polorejo is through intracurricular and extracurricular activities by modeling through stories, habituation and example. However, the value of the worship of alms (zakat, infaq, waqf) has not been prominent which has actually been implemented.